ANALISIS KANDUNGAN PROTEIN DAN LEMAK PADA KIMA RAKSASA(Tridacna gigas) DARI PERAIRAN PANTAI DESA SULI DAN DI INFORMASIKAN KEPADA MASYARAKAT MELALUI PENYULUHAN MENGGUNAKAN LEAFLET - Walsen, Patresya Salomina; Tuaputty, Hasan; Salmanu, Sriyanti Imelda A (Program Studi Pendidikan Biologi FKIP Unpatti, 2024)
Kima or giant clams (Giant Clams) are a type of bivalve that is often found in thewaters of shellfish ecosystems. Shellfish can be developed as a fishery resource with high nutritional value to meet people’s food needs. The main problem in this research is the protein and fat content of giant clams (Tridacna gigas) from the waters of Suli Village. The aim of this research is to determine the protein and fat content of giant clams (Tridacna gigas) from the waters of Suli Village. The method used in this research is descriptive to see the presence of protein and fat in Bivalves, giant clams (Tridacna gigas). Data from research on the analysis of protein content in giant clams (Tridacna gigas) resulted in a protein content of 11.0671 in the first repetition, 10.8958 in the second repetition, with an average prorein contente 0f 10.9814. meanwhile, the results of the analysis of the fat content of giant clams (Tridacna gigas) showed that the fat content was 0.7238 in the first repetition, 0.7005 in the second repetition, with an average fat content of 0.7121. using this research, the author hopes that this article will be useful for everyone who reads it and that the public will be able to find out the protein and fat content of the Giant kima (Tridacna gigas). And maintain theGiant Kima (Tridacna gigas) ecosystem found in the waters of Suli Village Beach.